2013
DOI: 10.1038/bjc.2012.550
|View full text |Cite
|
Sign up to set email alerts
|

Sexual quality of life in Hodgkin Lymphoma: a longitudinal analysis by the German Hodgkin Study Group

Abstract: Background:Health-related quality of life (HRQoL) comprises different domains of physical, mental, and social well-being. In this analysis, we focus on sexual quality of life in Hodgkin Lymphoma (HL) patients.Methods:Four-thousand one-hundred and sixty patients enroled in the HD10–HD12 trials underwent HRQoL assessment. Instruments included the Quality of Life Questionnaire for survivors (QLQ-S), combining the European Organisation for Research and Treatment of Cancer QLQ-C30, Multidimensional fatigue (FA) inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 42 publications
0
38
2
Order By: Relevance
“…As further observed within the final multivariate analysis, EORTC QLQ‐C30 role functioning was particularly impacted along with overall reduced QOL. Previous studies of patients with cancer have identified that the diagnosis of malignancy is associated with changes in relationship status, frequency of sexual activity, performance of daily activities, time spent in the home, and relationship status with family and friends . Within the MPN population, a patient's inability to fill previous gender‐related responsibilities such as managing the household, earning the family income, or providing care to other family members can be a source of significant distress that likely imparts a secondary impact on sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…As further observed within the final multivariate analysis, EORTC QLQ‐C30 role functioning was particularly impacted along with overall reduced QOL. Previous studies of patients with cancer have identified that the diagnosis of malignancy is associated with changes in relationship status, frequency of sexual activity, performance of daily activities, time spent in the home, and relationship status with family and friends . Within the MPN population, a patient's inability to fill previous gender‐related responsibilities such as managing the household, earning the family income, or providing care to other family members can be a source of significant distress that likely imparts a secondary impact on sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…33 Hence, this study adds to our findings that suggest that sexuality in patients older than 50 years treated for hematologic malignancies has to be further studied in larger samples to achieve more reliable data. Besides this, Kiserud et al 15 discussed that comorbidity and patients' experiences of poorer health need to be further explored in contrast to affected sexuality.…”
Section: Differences Between Baseline and Follow-up Scores For The Sumentioning
confidence: 75%
“…The risk of acute and long‐term toxicity might also be reduced. This is particularly important as late sequelae including infertility, heart failure and secondary solid and hematological malignancies do not only impair the quality of life but are also responsible for a relevant proportion of deaths among HL survivors .…”
Section: Discussionmentioning
confidence: 99%